1990
DOI: 10.1185/03007999009111492
|View full text |Cite
|
Sign up to set email alerts
|

Zuclopenthixol acetate(5% in ‘Viscoleo’): Single-dose treatment for acutely disturbed psychotic patients

Abstract: Twenty-five acutely disturbed psychotic patients were treated in an open study with a single injection of zuclopenthixol acetate 5% in 'Viscoleo, a thin vegetable oil. Patients were assessed post-injection for 3 days using the BPRS, CGI, and a specially designed behaviour/activity scale. Doses of 50 to 150 mg proved effective in 24 (96%) of 25 patients, with pronounced and rapid reduction in psychotic symptoms over the study period. The mean total BPRS score after 72 hours was reduced by over 57%. Tranquilliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…The levels gradually fall from this time and are at approximately one-third of the peak level at 72 h [1]. A number of open studies have demonstrated a reduction in Brief Psychiatric Rating Scale [6] scores during the 3-day period of action, including scores on psychotic items such as hallucinatory behaviour and unusual thought content [7,8]. This is consistent with the proportion of dopamine receptor blockade that is usually associated with antipsychotic efficacy in typical neuroleptics [3][4][5].…”
supporting
confidence: 54%
“…The levels gradually fall from this time and are at approximately one-third of the peak level at 72 h [1]. A number of open studies have demonstrated a reduction in Brief Psychiatric Rating Scale [6] scores during the 3-day period of action, including scores on psychotic items such as hallucinatory behaviour and unusual thought content [7,8]. This is consistent with the proportion of dopamine receptor blockade that is usually associated with antipsychotic efficacy in typical neuroleptics [3][4][5].…”
supporting
confidence: 54%
“…Although there are many studies suggesting the ecacy of zuclopenthixol acetate in the treatment of acute psychosis, most of these are limited by small sample sizes and open designs (Amdisen et al, 1986(Amdisen et al, , 1987Chakravarti et al, 1990;Bobon and De Bleeker, 1990;Matar et al, 1990;Chouinard et al, 1991;Farid et al, 1991;Schlosberg and Barr, 1991;Predescu et al, 1991;Baastrup et al, 1993;Tan et al, 1993). The only double-blind design was that of Chouinard et al (1994), who found the drugs to be of comparable ecacy, although more sedation was reported in the zuclopenthixol acetate group.…”
Section: Discussionmentioning
confidence: 99%
“…In open trials, zuclopenthixol acetate was found to be ecacious in the management of acute psychosis including mania and exacerbation of chronic schizophrenia. The most frequent sideeects of zuclopenthixol acetate reported were extrapyramidal such as tremor, rigidity, hypokinesia, dystonia and akathisia (Amdisen et al, 1986(Amdisen et al, , 1987Chakravarti et al, 1990;Chouinard et al, 1991;Bobon and De Bleeker, 1990;Matar et al, 1990;Farid et al, 1991;Schlosberg and Barr, 1991;Predescu et al, 1991;Baastrup et al, 1993;Tan et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…14 Changes in daily levels of alertness or sedation were assessed by the Tranquilization Scale, a modified 4-point scale in which a score of 1 corresponds to alertness, and a score of 4 corresponds to hypnosis (the patient sleeps and is not easily roused or, if roused, is unable to converse coherently). 18 A single item (vigilance) from the Cognitive Test for Delirium 19,20 was used daily to monitor for cognitive changes. It is a single-letter (''H'') auditory cancellation test that assesses attention; scoring reflects appropriate response to all mentions of this letter and absence of responding to other letters.…”
Section: Assessmentsmentioning
confidence: 99%